Quantifying the extent of climate inequality in China - Tan-Soo, Jie-Sheng; Chen, Shuai; Ye, Hai-Jian (Elsevier, 2023)
Using individual-level panel data representative of Chinese residents, this study examines in detail the relationship between temperature and subjective well-being (SWB). We first find that a 1 °C increase in temperature anomalies (difference between current and historical temperature) causes a 0.02 decrease in SWB (2% of 1 S.D.). Second, we present evidence of climate inequality along socioeconomic status (SES) as SWB of better educated, and higher-income Chinese residents are less affected by temperature anomalies compared to their lower SES counterparts. Closer examination reveals that adaptation mechanisms such as ownership of air-conditioners, automobiles, and indoor work help to alleviate adverse impacts of temperature anomalies. Lastly, for better comparison, we express our findings as monetized damages. We compute that a 1 °C increase in temperature anomalies causes damages equivalent to around 6.9% of income. However, these damages are mostly driven by Chinese from the lower-SES stratum as their damages are equivalent to around 9.6% of income compared to no damages for the high-SES group. Similarly, when translated into elasticity, we find that temperature-induced damages reduce by around 2% for every 1% increase in average income.